DYSFUNCTION OF COMPLEMENT SYSTEM IN FAMILIAL MEDITERRANEAN FEVER - G. M. Mkrtchyan; L. P. Hovhannisyan; A. A. Ayvazyan; E. Y. Nazaretyan; A. S. Boyajyan (Медицинская иммунология)
Abstract. During attacks of familial mediterranean fever (FMF), multiple systemic events are triggered, most of which promote autoinflammatory reactions. A molecular pattern of immune abnormalities in FMF is yet unclear. There is an increasing evidence to suggest an involvement of the complement system, the major inflammatory mediator, in FMF pathogeneses. In present study, we examined functional activities of the alternative and the classical complement cascades, and some relationships between alterations in the functional activities of these cascades in FMF. To this purpose, we measured hemolytic activities of classic (CH50) and alternative complement pathways (AH50), and of the complement components C3 (C3H50), factor B (fBH50) and factor D (fDH50) in blood serum of twenty-eight colchicine-free FMF patients and twenty-five healthy subjects. According to the data obtained, a decrease in serum levels of AH50 and increase in CH50 and C3H50 were detected in FMF patients, as compared to normal values. No significant difference was detected between the affected persons and healthy subjects for fBH50 and fDH50. Correlation analysis revealed a positive relationship between alterations in CH50 and C3H50 and a negative correlation between alterations in AH50 and CH50. From the data obtained, following conclusions have been made: 1) pathogenesis of FMF is characterized by a complement dysfunction, including hyperactivation of classical complement pathway and hypoactivation state of alternative pathway; 2) alterations in functional activities of classical and alternative complement activation pathways in FMF are interdependent; 3) the alternative pathway is suppressed on the initial stage of its activation; 4) high blood levels of C-reactive protein, serum amyloid P component, and circulating immune complexes, associated with FMF, might be responsible for hyperactivation of classical complement pathway in this disease.